The effect of pine oil on some alterations in liver tissue of experimental diabetes - Demir, Ersin; Yilmaz, Ökkeş (Refik Saydam National Public Health Agency (RSNPHA), 2014)
Objective: The present study was designed to evaluate the impact of pine oil on MDA (malondialdehyde), GSH (glutathione), total protein, fatty acid composition, ADEK vitamins, cholesterol and some sterols parameters in liver tissue of experimental diabetes in rats. Method: The rats were divided into three groups: control (C) streptozotocin (STZ), streptozotocin (STZ) + pine oil (PO) groups. Diabetes induced in rats by a single intraperitoneal injection of streptozotocin (45 mg/kg). 1 mL/kg dose pine oil was intraperitoneally injected twice in a week to the streptozotocin (STZ) + pine oil (PO), and additionally 0.5 mL/500 mL dose of pine oil was added to drinking water of this group. The experiment continued for eight weeks. Results: It was observed that MDA and total protein levels were significantly increased (p<0.001), GSH level was significantly decreased (p<0.001) in the liver tissue of STZ group when compared to the control group. It was detected that MDA and GSH levels were significantly decreased (p<0.001) in the liver tissue of STZ + PO group when compared to the STZ group. It was determined that palmitic, palmitoleic (p<0.001) and arachidonic acid (p<0.01) levels were significantly decreased, stearic, linoleic (p<0.001) and docosahexaenoic acid (p<0.05) levels were significantly increased in the liver tissue of STZ group when compared to the control group. It was detected that stearic and arachidonic (p<0.001) acid levels were significantly decreased, palmitic, palmitoleic, oleic, linoleic, a-linolenic and docosahexaenoic acid levels were significantly increased (p<0.001) in the liver tissue of STZ + PO group when compared to the STZ group. It was observed that ?-tocopherol and vitamin D2 levels were significantly decreased (p<0.001), vitamin D3 (p<0.05), vitamin K2, a-tocopherol, retinol, vitamin K1, cholesterol, stigmasterol and ß-sitosterol levels were significantly increased (p<0.001) in the liver tissue of STZ group when compared to the control group. It was determined that vitamin K2, vitamin D3, a-tocopherol, vitamin K1, ß-sitosterol (p<0.001) and cholesterol (p<0.05), levels were significantly increased, d-tocopherol and stigmasterol levels were significantly decreased (p<0.001) in the liver tissue of STZ + PO group when compared to the STZ group. Conclusion: It was determined that the application of pine oil was of limited effect on the metabolic disorders of GSH, total protein, some fatty acid composition and ADEK vitamins in the liver tissue of experimental diabetic rats.
Deneysel diyabetin karaciğer dokusunda oluşturduğu bazi değişiklikler üzerine çam yağinin etkisi
Keywords: ADEK vitamins; Cholesterol; Experimental diabetes; Fatty acid composition; Lipid peroxidation; Liver; Sterols